Subacute inflammatory processes and Chronic Bronchopulmonary: SIMPOSIUM - Martínez, José Luis; Puig, Roberto M; Delbene, Roberto; Bordes, Daniel; Rivas Chetto, C.; Zubiaurre, J; Stratta, A.; di Trápani, N; Sciuto, F; Louzán, R (Cirugía del Uruguay, 2004)
Introducción Jose Luis MartinezIn 32 years of experience in Thoracic Surgery(1970 - 2002) we have operated 56 patients forsubacute and chronic bronchopulmonary inflammatory processes.In that period we have treated 21primitive pulmonary suppurations and 35 bronchiectasis.Despite their different origins all theseentities have pathological alterationscommon where fibrosis predominates, dilationsbronchial, presence of cavities and circulationanomalous systemic that are at the baseof suppurative clinical manifestations,hemorrhagic or secondary aspergillary fungal infection.